Investigating students’ development of mechanistic reasoning in modeling complex aquatic ecosystems - Ryan, Zach; Danish, Joshua; Zhou, Jinzhi; Stiso, Christina; Murphy, Danielle; Duncan, Ravit; Chinn, Clark; Hmelo-Silver, Cindy E. (Frontiers in Education, 2023)
Scientific modeling and complex systems thinking are two critical aspects of scientific inquiry that young students often struggle to engage in. In response to these challenges, researchers have endeavored to integrate these concepts to better support young students’ learning about complex science phenomena. This study reports on findings situated in a scientific modeling unit where students worked to model a complex system. This study and the larger project it is a part of worked alongside late elementary students and their teacher to integrate the two topics by embedding a systems thinking conceptual framework into a scientific modeling tool and set of activities. We report on a designed software tool, which explicitly scaffolded key elements of biological systems within its interface, and allowed students to create and refine models of complex systems. The aim of this study is to examine how students utilizing this tool were supported in developing their mechanistic reasoning when modeling complex systems.